2012
DOI: 10.1063/1.4719688
|View full text |Cite
|
Sign up to set email alerts
|

Lithium-based surfaces controlling fusion plasma behavior at the plasma-material interface

Abstract: The plasma-material interface and its impact on the performance of magnetically confined thermonuclear fusion plasmas are considered to be one of the key scientific gaps in the realization of nuclear fusion power. At this interface, high particle and heat flux from the fusion plasma can limit the material's lifetime and reliability and therefore hinder operation of the fusion device. Lithium-based surfaces are now being used in major magnetic confinement fusion devices and have observed profound effects on pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 47 publications
2
7
0
Order By: Relevance
“…Ex-Situ analysis of samples exposed to lithium, using DiMES, indicated that lithium once deposited, can diffuse or intercalate to depths up to 1000 nm. This is consistent with observations from other work [10,13]. In addition, 25 graphite samples exposed during the entire 2013 campaign showed that lithium deposited in the tiles was very non-uniform, consistent with observations by MDS.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Ex-Situ analysis of samples exposed to lithium, using DiMES, indicated that lithium once deposited, can diffuse or intercalate to depths up to 1000 nm. This is consistent with observations from other work [10,13]. In addition, 25 graphite samples exposed during the entire 2013 campaign showed that lithium deposited in the tiles was very non-uniform, consistent with observations by MDS.…”
Section: Discussionsupporting
confidence: 92%
“…We note that the direction of SOL flow discussed above is consistent with previous DIII-D 13 C experiments [12].…”
Section: Migration Of Lithium To Pfcssupporting
confidence: 90%
See 2 more Smart Citations
“…This dramatic increase in surface oxygen content during deuterium bombardment is surprising, and leads to unexpected consequences for the deuterium chemistry. In particular we found that when lithiated carbon is bombarded with low-energy deuterium ions ( 50-500 eV), significant chemical shifts in the oxygen XPS photoelectron O1s spectrum are observed experimentally [14,17,[21][22][23]. The chemical changes were observed as stronger shifts in the O1s spectra when compared to those found in Li1s and C1s XPS spectra for lithiated carbon (and also compared to laboratory XPS experiments with lithium- only foils [21]), challenging the notion that the uptake of deuterium occurred by hydride bonding with lithium atoms.…”
mentioning
confidence: 86%